Early-pregnancy percent body fat in relation to preeclampsia risk in obese women - Sween, Lindsay K.; Althouse, Andrew D.; Roberts, James M. (American journal of obstetrics and gynecology, 2015)
The purpose of this study was to identify differences of early-pregnancy body fat percentage and body mass index (BMI) between obese women that experienced preeclampsia and those who did not. We performed an analysis of the Prenatal Exposures and Preeclampsia Prevention 3 longitudinal cohort study of preeclampsia mechanisms in obese and overweight women. Women completed questionnaires regarding their health behaviors; had hematocrit level, weight and height, and waist and hip circumferences measured, and had resistance and reactance measured by bioelectric impedance analysis machine during the first, second, and third trimesters. Total body water, fat mass, and percent body fat were calculated with the use of pregnancy-specific formulas. Preeclampsia was assessed with the clinical definition and a research definition (clinical preeclampsia plus hyperuricemia). Logistic regression models were constructed to analyze early-pregnancy BMI and body fat percentage (measured at 10.2 ± 3.0 weeks of gestation) as predictors of preeclampsia outcomes. Three hundred seventy-three women were included in the analysis: 30 women had preeclampsia by clinical definition (8.0%), and 14 women had preeclampsia by the research definition (3.8%). There was no relationship between BMI and preeclampsia risk in obese women; however, body fat percentage was associated significantly with increased risk of both the clinical definition of preeclampsia and the research definition. In 239 obese women, a 1% increase in body fat was associated with approximately 12% increased odds of clinical preeclampsia and 24% increased risk of preeclampsia by the research definition. Early-pregnancy body fat appears to be important in the pathophysiologic condition of preeclampsia in obese women.